2021
DOI: 10.4149/bll_2021_047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluid resuscitation on acute lung injury in a rat model of sepsis

Abstract: AIM: Sepsis is a systemic infection reaction and intravascular volume therapy plays a crucial role in it's treatment. Acute respiratory distress syndrome (ARDS) occurs in the lungs, the most affected organ. This study aimed to investigate the different effects of fl uid therapy on ARDS caused by sepsis. METHOD: To form a sepsis model, cecal ligation and puncture (CLP) procedure were performed on 44 adult rats. Divided into six groups; normal, CLP group, those treated with 40 ml/kg 0.9 % NaCl, 3 % NaCl (hyperto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…After ischemia, the intestinal tract releases pro-inflammatory molecules, such as superoxide anion free radicals and cytokines, causing the intestinal flora to shift and enter the portal vein and systemic circulatory system, leading to intestinal remote organ failure 41,42 . A study has shown that HES-130 infusion inhibits the release of pro-inflammatory cytokines, such as tumor necrosis factor α and interleukin 6, 43 which may be the reason for the improvement in intestinal barrier dysfunction 44–46 . Our new type of oxygen-carrying plasma can be used for the treatment of severe acute pancreatitis through the mechanism of HES by improving intestinal oxygen metabolism, reducing the release of inflammatory mediators, and protecting the integrity of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After ischemia, the intestinal tract releases pro-inflammatory molecules, such as superoxide anion free radicals and cytokines, causing the intestinal flora to shift and enter the portal vein and systemic circulatory system, leading to intestinal remote organ failure 41,42 . A study has shown that HES-130 infusion inhibits the release of pro-inflammatory cytokines, such as tumor necrosis factor α and interleukin 6, 43 which may be the reason for the improvement in intestinal barrier dysfunction 44–46 . Our new type of oxygen-carrying plasma can be used for the treatment of severe acute pancreatitis through the mechanism of HES by improving intestinal oxygen metabolism, reducing the release of inflammatory mediators, and protecting the integrity of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 A study has shown that HES-130 infusion inhibits the release of pro-inflammatory cytokines, such as tumor necrosis factor α and interleukin 6, 43 which may be the reason for the improvement in intestinal barrier dysfunction. [44][45][46] Our new type of oxygen-carrying plasma can be used for the treatment of severe acute pancreatitis through the mechanism of HES by improving intestinal oxygen metabolism, reducing the release of inflammatory mediators, and protecting the integrity of the intestinal barrier. Reducing the body's oxidative stress and inflammation while reducing the translocation of intestinal bacteria, combined with PolyHb, can increase the oxygen supply of the intestinal mucosa and other important organs and its synergistic effect in improving the mesenteric microcirculation.…”
Section: Limitations and Prospectsmentioning
confidence: 99%
“…Luteolin administration decreased the expression of TNF-α and IL-10 mRNA in lung tissue. Moreover, luteolin was shown to attenuate sepsis-induced acute lung injury in mice by inhibiting intercellular adhesion molecule (ICAM)-1, NF-κB, oxidative stress, and part of the iNOS pathway [54,55]. Luteolin could be an effective candidate to treat HgCl 2 -induced lung injury by blocking NF-κB activation and activating the AKT/Nrf2 pathway.…”
Section: Lung Injurymentioning
confidence: 99%
“…Sepsis is a pathological condition characterized by the host's dysregulated inflammatory response to an infection 1,2 . This dysregulation manifests as an imbalance between proinflammatory and anti-inflammatory factors, resulting in tissue damage and the subsequent development of multiple organ dysfunction and failure [3][4][5] . Sepsis continues to be the primary contributor to morbidity and mortality in intensive care units (ICUs) globally 6,7 .…”
Section: Introductionmentioning
confidence: 99%